Opportunities and Prospects for Preclinical Drug Safety Assessment Using Alternative Methods: Experience from the Toxicology in the 21st Century (Tox21) Programme in the USA - V. N. Perfilova (Безопасность и риск фармакотерапии)
SCIENTIFIC RELEVANCE. The Tox21 (Toxicology in the 21st Century) programme was developed by the US Tox21 Consortium with the aim to replace animal-based toxicity assessments of chemicals with a wide range of in vitro and in silico testing approaches and has since been successfully applied in practice.AIM. The study aimed to review information on alternative in vitro models developed as part of the Tox21 programme for testing the toxicity of chemical compounds.DISCUSSION. According to the information provided by the National Toxicology Program, Environmental Protection Agency, National Center for Advancing Translational Sciences, and other Tox21 Consortium members on their official websites and in the literature, the Tox21 Consortium has developed a quantitative high-throughput screening technology for testing the safety of chemicals and created the Tox21 10K library of chemical compounds using this screening technology. The library has been successfully used to create models that predict the toxicity of chemicals prior to preclinical studies. Researchers have proposed new approaches to studying the safety of chemical compounds in human cell lines to replace in vivo studies. Innovative organ-on-chip, multi-organ-on-chip, and organoid models are free from the drawbacks and limitations of cell-line models and offer more accurate representations of complex cell–matrix and organ–organ interactions. Developed under the Tox21 programme to search for new chemical toxicity biomarkers and gene signatures, novel transcriptomics (toxicogenomics) technologies can be used to classify toxicants according to their health risks and to identify potential side effects long before discovering any pathological changes in the body. The Interagency Coordinating Committee on the Validation of Alternative Methods conducts technical evaluation of alternative testing methods and promotes their implementation into regulatory practice.CONCLUSIONS. Thus, new tools and technologies provide an opportunity for switching from in vivo toxicity testing of candidate medicinal products to in silico and in vitro methods.